The Douglas County Drug Court: A Comparison of Recidivism Rates Between Drug Court Participants and Traditionally Adjudicated Drug Offenders - Frenzel, Erika Davis (2000)
Over the years there have been large increases in the number of drug offenders arrested, prosecuted, and sentenced to prison. These increases have lead to an overload of the criminal justice system. This overload prompted states to develop new responses to substance use and drug-related crime. One such innovation is the drug treatment court, which combines accountability and treatment. The goal of these courts is to reduce recidivism and substance use among drug-involved criminal offenders. This study uses data from Douglas County (Nebraska) to compare recidivism rates for participants in the Douglas County Drug Court and traditionally adjudicated drug offenders. The overall objective was to determine if the Douglas County Drug Court was more effective at reducing recidivism rates as compared to traditionally adjudicated drug offenders. This study found that drug court participants who graduated or were active in the drug court had lower recidivism rates than traditionally adjudicated offenders